STRATEGI PENGEMBANGAN WILAYAH PERBATASAN NUSA TABUKAN KABUPATEN KEPULAUAN SANGIHE BERBASIS EKOWISATA BAHARI - Lesawengen, Juita Carolina (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
Nusa Tabukan in Sangihe Islands Regency is a cluster of small islands at the outer teritorry, consist of four islands that located in the northern part on Sangihe Island.The aims of this research were to identify potential tourist attractions, analyzing internal and external factors, and formulating proper marine ecotourism strategies and programs.The results indicate that potentials attractions can be developed at Nusa Tabukan. Those are the nature and socio-culture environment.Small islands, white sandy beaches, coral reefs, mangrove forest, sea grass, dugong¸local wisdom as well as economic activities on community can be developed as marine tourism attractions.However, there were some obstacles related to tourism development such as human resources, tourism facilities and infrastructure and accessibility.This research formulated the grand strategy S-O to be applied which is strategy of marine ecotourism development in border cross area, while alternative strategies are also formulated.Roles of relates stakeholder is necessary needed to ensure the development is on the right track of sustainability.
Keywords: development, marine ecotourism, border cross tourism